Long-/Post-COVID-Beschwerden in einem Hotspot-Kollektiv der ersten Infektionswelle in Deutschland - Wolfschmidt, Anna; Ott, Stephan; Richter, Steffi; Schmidt, Johannes; Uter, Wolfgang; Drexler, Hans; Finkenzeller, Thomas (Zeitschrift für Evidenz, Fortbildung und Qualitat im Gesundheitswesen, 2024)
Introduction: Despite a high number of long/post-COVID cases and an enormous psychological strain on the part of the patients, no scientific consensus has yet been reached on a clearly defined disease entity. The comprehensive media coverage has made the public more sensitive to this topic, which makes it more difficult to take an objective perspective. Methods: We report on long/post-COVID symptoms in a hotspot collective of the first SARS-CoV-2 wave of infections in Germany; these infections began in Spring 2020 and therefore preceded the start of an intensive media coverage. In June/July 2021, 122 employees of the Kliniken Nordoberpfalz AG who tested positive for SARS-CoV-2 during the first wave of the pandemic were asked about their infection and its consequences using a standardised questionnaire. Results: 82 participants (67 %) complained of persistent symptoms (post-COVID: 29 %). Long/post-COVID symptoms occurred more frequently in those who had experienced symptoms during the acute phase of the infection. Patients with stomach pain as an acute symptom more frequently reported a symptom duration of > 12 weeks. The probability of symptoms persisting > 12 weeks was reduced if throat pain or sniffling had been reported as an acute symptom. Emergence and duration of symptoms were independent of any demographic or occupational factors or of pre-existing conditions. Discussion: Due to having been infected in a hotspot region during the first wave of the pandemic, the study collective exhibits certain peculiarities which must be considered when interpreting the results. The lack of evidence for many risk factors discussed in the literature, together with the challenges facing scientific studies, seems to suggest a more differentiated approach to dealing with post-COVID.
CRIS-Team Scopus Importer:2024-11-29
Keywords: COVID sequelae; First wave; Long-COVID; Post-COVID; Risk factor; SARS-CoV-2